Endoscopic submucosal dissection techniques and technology: European Society of Gastrointestinal Endoscopy (ESGE) Technical Review - Libânio, Diogo; Pimentel-Nunes, Pedro; Bastiaansen, Barbara; Bisschops, Raf; Bourke, Michael J.; Deprez, Pierre H.; Esposito, Gianluca; Lemmers, Arnaud; Leclercq, Philippe; Maselli, Roberta; Messmann, Helmut; Pech, Oliver; Pioche, Mathieu; Vieth, Michael; Weusten, Bas L.A.M.; Fuccio, Lorenzo; Bhandari, Pradeep; Dinis-Ribeiro, Mario (Endoscopy, 2023)
ESGE suggests conventional endoscopic submucosal dissection (ESD; marking and mucosal incision followed by circumferential incision and stepwise submucosal dissection) for most esophageal and gastric lesions. ESGE suggests tunneling ESD for esophageal lesions involving more than two-thirds of the esophageal circumference. ESGE recommends the pocket-creation method for colorectal ESD, at least if traction devices are not used. The use of dedicated ESD knives with size adequate to the location/thickness of the gastrointestinal wall is recommended. It is suggested that isotonic saline or viscous solutions can be used for submucosal injection. ESGE recommends traction methods in esophageal and colorectal ESD and in selected gastric lesions. After gastric ESD, coagulation of visible vessels is recommended, and post-procedural high dose proton pump inhibitor (PPI) (or vonoprazan). ESGE recommends against routine closure of the ESD defect, except in duodenal ESD. ESGE recommends corticosteroids after resection of  > 50 % of the esophageal circumference. The use of carbon dioxide when performing ESD is recommended. ESGE recommends against the performance of second-look endoscopy after ESD. ESGE recommends endoscopy/colonoscopy in the case of significant bleeding (hemodynamic instability, drop in hemoglobin > 2 g/dL, severe ongoing bleeding) to perform endoscopic hemostasis with thermal methods or clipping; hemostatic powders represent rescue therapies. ESGE recommends closure of immediate perforations with clips (through-the-scope or cap-mounted, depending on the size and shape of the perforation), as soon as possible but ideally after securing a good plane for further dissection.